Modified lithium cobalt oxide cathode material, preparation method and application thereof
Patent Information
- Application Number
- CN202611223275.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-12
- Publication Date
- 2026-10-16
AI Technical Summary
但存在明显缺陷:单一元素掺杂易产生晶格缺陷与杂相杂质,掺杂均匀性差,无法兼顾高压稳定性与导电性能;单一表面包覆存在包覆层厚薄不均、结合力弱、高温易脱落、离子导电性差等问题,难以适配长期高压循环工况;常规工艺优化对材料本征结构缺陷改善效果有限
本发明提供的改性钴酸锂正极材料,通过在商业化钴酸锂(LCO)基体表面形成稀土包覆层,并使至少部分稀土元素进入其晶格内部,由此构建出贯穿表面至体相的协同稳定结构,稀土包覆层作为物理与化学屏障,可在材料表面构建防护层,隔绝电解液与活性基底的直接接触,抑制界面副反应与钴溶出;晶格内部的稀土元素则有助于维持层状结构在高电压循环中的完整性,延缓容量衰减趋势。本发明提供的改性钴酸锂正极材料同步实现体相与界面双重优化效果,使材料的储能性能全面提升。
Smart Images

Figure CN122930878A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of lithium-ion battery cathode materials technology, and in particular to a modified lithium cobalt oxide cathode material, its preparation method, and its application. Background Technology
[0002] Lithium-ion batteries have become the mainstream electrochemical energy storage device in consumer electronics (smartphones, laptops, tablets), smart wearables, portable energy storage, and small power supplies due to their advantages such as high energy density, long cycle life, no memory effect, and environmental friendliness. Among them, lithium cobalt oxide (LiCoO2, LCO), as the earliest commercially available layered cathode material, has long dominated the high-end consumer battery market due to its regular hexagonal lattice structure, high electronic conductivity, high compaction density, and mature manufacturing process. Standard commercial lithium cobalt oxide materials typically operate at a voltage of 3.0-4.2 V, with a theoretical specific capacity of up to 274 mAh g⁻¹. -1 The actual stable and reversible specific capacity is approximately 150 mAh g. -1 .
[0003] With the increasing demand for thinner and lighter consumer electronics, longer battery life, and fast charging, as well as the development of emerging applications such as smart wearables, drones, and portable energy storage, the market is placing higher demands on the energy density, high-voltage tolerance, high-temperature cycle stability, and rate performance of lithium-ion batteries. Raising the charging cutoff voltage of lithium cobalt oxide batteries to 4.6V can significantly improve their reversible capacity, which is the most direct and effective way to increase energy density.
[0004] However, unmodified pure-phase lithium cobalt oxide materials have many inherent structural defects, severely limiting their large-scale application under high-voltage conditions. The layered crystal structure of lithium cobalt oxide has poor stability. During high-voltage charging and discharging, the rapid insertion and extraction of lithium ions triggers an irreversible phase transition from the hexagonal to the monoclinic and cubic phases, causing lattice distortion, layered structure collapse, significant volume expansion, and stress accumulation, leading to electrode pulverization and detachment. Furthermore, under high-voltage conditions, the electrolyte activity increases significantly, readily reacting violently with the lithium cobalt oxide cathode surface, continuously corroding the material surface and causing substantial dissolution and loss of cobalt. This not only reduces the utilization rate of active materials but also leads to electrolyte decomposition and gas generation, continuously increasing battery internal resistance, and in severe cases, causing battery bulging and thermal runaway, posing significant safety hazards. Pure-phase lithium cobalt oxide has high interfacial impedance, limiting lithium-ion migration rates under fast charging conditions, resulting in poor rate charge / discharge performance. Moreover, its capacity decays rapidly during high-temperature cycling, significantly shortening its lifespan.
[0005] To address the aforementioned technical challenges, the current mainstream modification strategies in the industry include bulk doping (such as Al). 3+ Mg 2+ Ti 4 +), surface coating and process optimization. However, there are obvious drawbacks: single-element doping is prone to lattice defects and impurities, poor doping uniformity, and cannot take into account both high-voltage stability and conductivity; single surface coating has problems such as uneven coating thickness, weak bonding force, easy detachment at high temperature, and poor ionic conductivity, making it difficult to adapt to long-term high-voltage cycling conditions; conventional process optimization has limited effect on improving the intrinsic structural defects of the material.
[0006] Furthermore, most existing modification technologies employ multi-step preparation processes involving stepwise doping and coating. These processes require the introduction of dopant elements at the raw material (lithium salt, cobalt salt) stage, resulting in cumbersome procedures, high energy consumption, poor modification uniformity, weak bonding between the doped and coated layers, and susceptibility to problems such as coating layer detachment and modification failure during cycling. This leads to poor process repeatability and mass production. For example, CN106277070A uses a source synthesis route, employing lithium carbonate and cobalt oxide as raw materials, adding MgO, Al2O3, or Nd2O3, etc., followed by a first high-temperature sintering, surface treatment, secondary mixing, and a second high-temperature sintering (1000-1050℃). This process involves numerous steps and high energy consumption. CN121964626A is a high-entropy doped material, requiring the simultaneous introduction of six elements—Mg, Al, Ti, Sn, Sb, and F—at the lithium / cobalt raw material stage. It cannot be directly used in commercially available lithium cobalt oxide powders and lacks the potential for further performance improvements in existing commercial lithium cobalt oxide products.
[0007] In view of this, the present invention is proposed. Summary of the Invention
[0008] One of the objectives of this invention is to provide a modified lithium cobalt oxide cathode material to at least solve one of the technical problems existing in the prior art.
[0009] The second objective of this invention is to provide a method for preparing a modified lithium cobalt oxide cathode material.
[0010] The third objective of this invention is to provide a modified lithium cobalt oxide cathode material or a modified lithium cobalt oxide cathode material prepared by the aforementioned preparation method, and its application in the preparation of lithium-ion batteries.
[0011] In order to achieve the above-mentioned objectives of the present invention, the following technical solution is adopted: In a first aspect, the present invention provides a modified lithium cobalt oxide cathode material, wherein the modified lithium cobalt oxide cathode material uses commercial lithium cobalt oxide as a matrix, the surface of the commercial lithium cobalt oxide has a rare earth coating layer, and at least some rare earth elements are incorporated into the crystal lattice of the commercial lithium cobalt oxide.
[0012] Furthermore, the rare earth coating layer includes one or more of La2O3, CeO2, Gd2O3, and Y2O3.
[0013] Furthermore, the particle size of the lithium cobalt oxide cathode material is 2-20 µm; Preferably, the thickness of the rare earth coating layer is 3-8 nm, and more preferably 3-5 nm.
[0014] In a second aspect, the present invention provides a method for preparing a modified lithium cobalt oxide cathode material, comprising: (a) A rare earth source is mixed with commercial lithium cobalt oxide to obtain a mixture; (b) The mixture is subjected to heat treatment to obtain the modified lithium cobalt oxide cathode material.
[0015] Furthermore, the rare earth source includes rare earth oxides and / or rare earth nitrates; Preferably, the rare earth oxide includes one or more of La2O3, CeO2, Gd2O3, and Y2O3; Preferably, the rare earth nitrate includes one or more of La(NO3)3, Ce(NO3)4, Gd(NO3)3 and Y(NO3)3.
[0016] Furthermore, the rare earth source accounts for 0.1%-3% of the total mass of the mixture, more preferably 0.5%-2%.
[0017] Furthermore, in step (a), the mixing is carried out in the presence of a dispersant, which includes at least one of ethanol and deionized water; Preferably, in step (a), the mixing time is 10-240 min; the mixing method includes ball milling and / or ultrasonic treatment, and the ball milling speed is 400-1200 r / min.
[0018] Furthermore, in step (b), the heat treatment includes: heating to a target temperature and then holding at that temperature; Preferably, the target temperature is 400-800℃, the heating rate is 3-10℃ / min, and the holding time is 2-12 h.
[0019] Furthermore, after the heat treatment, a post-treatment is also included; the post-treatment includes at least one of ball milling, washing, centrifugation and drying; Preferably, the ball mill rotates at a speed of 400-800 r / min for 10-240 min. Preferably, the drying temperature is 60-100°C.
[0020] Thirdly, the present invention provides an application of a modified lithium cobalt oxide cathode material or a modified lithium cobalt oxide cathode material prepared by the aforementioned preparation method in the preparation of lithium-ion batteries.
[0021] Compared with the prior art, the present invention has the following beneficial effects: The modified lithium cobalt oxide cathode material provided by this invention achieves a synergistic stable structure spanning from the surface to the bulk phase by forming a rare earth coating layer on the surface of a commercial lithium cobalt oxide (LCO) substrate and allowing at least some rare earth elements to enter its crystal lattice. The rare earth coating layer acts as a physical and chemical barrier, forming a protective layer on the material surface that isolates the electrolyte from direct contact with the active substrate and suppresses interfacial side reactions and cobalt dissolution. The rare earth elements within the crystal lattice help maintain the integrity of the layered structure during high-voltage cycling, delaying capacity decay. The modified lithium cobalt oxide cathode material provided by this invention simultaneously achieves dual optimization of the bulk phase and interface, resulting in a comprehensive improvement in the material's energy storage performance. Attached Figure Description
[0022] To more clearly illustrate the specific embodiments of the present invention or the technical solutions in the prior art, the drawings used in the description of the specific embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For those skilled in the art, other drawings can be obtained from these drawings without creative effort.
[0023] Figure 1 TEM images of the original commercial LCO cathode material in Example 1 and the rare earth modified LCO cathode material prepared in Example 1; Figure 2 The first charge-discharge curves of the original commercial LCO cathode material in Example 1 and the rare earth modified LCO cathode material prepared in Example 1 are shown. Figure 3 The cycle discharge capacity curves of the original commercial LCO cathode material in Example 1 and the rare earth modified LCO cathode material prepared in Example 5 are shown. Figure 4 The rate discharge capacity diagrams are for comparing the original commercial LCO cathode material of Example 1 with the rare earth modified LCO cathode material prepared in Example 1. Figure 5 SEM image of the original commercial LCO cathode material; Figure 6 This is a SEM image of the rare earth modified LCO cathode material prepared in Example 1. Detailed Implementation
[0024] Unless otherwise defined herein, the scientific and technical terms used in conjunction with this invention shall have the meanings commonly understood by one of ordinary skill in the art. The meaning and scope of terms shall be clear; however, in any case of potential ambiguity, the definitions provided herein shall prevail over any dictionary or foreign definitions. In this application, unless otherwise stated, the use of "or" means "and / or". Furthermore, the use of the term "comprising" and other forms is non-limiting.
[0025] The technical solution of the present invention will be clearly and completely described below with reference to the embodiments. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0026] The present invention provides a modified lithium cobalt oxide cathode material, wherein the modified lithium cobalt oxide cathode material uses commercial lithium cobalt oxide as a matrix, the surface of the commercial lithium cobalt oxide is coated with a rare earth coating layer, and at least some rare earth elements are incorporated into the crystal lattice of the commercial lithium cobalt oxide.
[0027] This invention aims to simplify the modification and preparation process and reduce production costs. It utilizes the unique physicochemical properties of rare earth elements to synergistically optimize the bulk crystal structure and surface interface characteristics of LCO, effectively solving the technical problems of traditional LCO such as rapid cycle decay under high voltage, severe interfacial side reactions, and poor rate performance. Without sacrificing the energy density of the material, it significantly improves the structural stability, ionic conductivity, high voltage tolerance, and long cycle life of LCO cathode materials, making it suitable for the application requirements of high-voltage, fast charging, and long battery life of high-end electronic devices.
[0028] The preparation method of the modified lithium cobalt oxide cathode material includes the following steps: (a) A rare earth source is mixed with commercial lithium cobalt oxide to obtain a mixture; (b) The mixture is heat-treated to obtain the modified lithium cobalt oxide cathode material.
[0029] This invention proposes a one-step rare-earth method for simultaneously achieving dual modification of lithium cobalt oxide through doping and coating. Using commercially available LCO products as the substrate material, a single-step heat treatment process allows nano-sized rare-earth raw materials to form a uniform and dense rare-earth coating layer in situ on the surface of LCO particles. Simultaneously, some rare-earth ions spontaneously infiltrate into the lithium cobalt oxide lattice under high temperature to complete bulk doping, achieving a dual modification effect of surface coating protection and bulk lattice stabilization. The modified lithium cobalt oxide cathode material provided by this invention exhibits long-term cycle stability at high operating voltages.
[0030] Cerium, a rare earth element, possesses a unique electronic structure, variable valence state characteristics, extremely high lattice binding energy, and chemical stability, making it a high-quality functional element for modifying lithium-ion battery cathodes. Compared to conventional modifying metals, rare earth elements offer significant advantages: Firstly, their ionic radius closely matches that of cobalt ions, allowing them to easily embed into the lithium cobalt oxide lattice without extreme conditions. This replaces some cobalt sites, effectively reinforcing the layered crystal structure, suppressing lattice distortion and irreversible phase transitions during charge and discharge, and significantly improving the bulk structural stability of the material. Secondly, rare earth elements readily form a dense, stable, and highly conductive rare earth oxide coating layer on the surface of lithium cobalt oxide particles. This physically isolates the electrolyte from the cathode substrate, effectively suppressing interfacial side reactions, cobalt dissolution, and electrolyte decomposition, significantly improving the material's high-temperature and high-pressure cycling performance. Furthermore, the rare earth coating layer exhibits excellent ion conductivity, reducing electrode interfacial impedance, increasing lithium-ion migration rate, and improving the material's fast-charging performance.
[0031] Compared to traditional stepwise modification processes, this invention uses nano-scale rare earth oxides (<100 nm) and / or rare earth nitrates as raw materials, and for the first time clearly proposes to achieve simultaneous doping-coating synergistic modification in commercial lithium cobalt oxide cathode materials through a one-step sintering method, thereby improving the energy storage performance of the material under high cutoff voltage (4.6 V) conditions, especially improving the cycle life by more than 50%.
[0032] Furthermore, based on mature commercial lithium cobalt oxide materials, this invention improves production efficiency by selecting raw materials, simplifying the modification process, and especially optimizing the initial dispersion process, making the energy conditions required for modification more moderate and adapting to large-scale industrial production standards.
[0033] In some preferred embodiments, the rare earth coating layer includes one or more of La2O3, CeO2, Gd2O3, and Y2O3.
[0034] In some preferred embodiments, the particle size of the lithium cobalt oxide cathode material is 2-20 µm, wherein the thickness of the rare earth coating layer is 3-8 nm, more preferably 3-5 nm.
[0035] In some preferred embodiments, the rare earth source includes rare earth oxides and / or rare earth nitrates; Preferably, the rare earth oxide includes one or more of La2O3, CeO2, Gd2O3, and Y2O3; Preferably, the rare earth nitrate includes one or more of La(NO3)3, Ce(NO3)4, Gd(NO3)3 and Y(NO3)3.
[0036] In some preferred embodiments, the rare earth source accounts for 0.1%-3% of the total mass of the mixture, for example, it can be 0.1%, 0.5%, 1%, 2%, 3%, etc., and more preferably 0.5%-2%.
[0037] In some preferred embodiments, in step (a), the mixing is carried out in the presence of a dispersant, which includes at least one of ethanol and deionized water.
[0038] Preferably, in step (a), the mixing time is 10-240 min, for example, it can be 10 min, 50 min, 100 min, 150 min, 200 min, 240 min, etc.; the mixing method includes ball milling and / or ultrasonic treatment, and the rotation speed of the differential ball mill is 400-1200 r / min, for example, it can be 400 r / min, 600 r / min, 800 r / min, 1000 r / min, 1200 r / min, etc.
[0039] In some preferred embodiments, step (b) includes heating to a target temperature and then holding at that temperature. The target temperature is 400-800℃, for example, 400℃, 500℃, 600℃, 700℃, 800℃, etc.; the heating rate is 3-10℃ / min, for example, 3℃ / min, 4℃ / min, 5℃ / min, 6℃ / min, 7℃ / min, 8℃ / min, 9℃ / min, 10℃ / min, etc.; and the holding time is 2-12 h, for example, 2 h, 4 h, 6 h, 8 h, 10 h, 12 h, etc.
[0040] In some preferred embodiments, the heat treatment is followed by a post-treatment; the post-treatment includes at least one of ball milling, washing, centrifugation, and drying; wherein the ball milling speed is 400-800 r / min, for example, 400 r / min, 600 r / min, 800 r / min, etc., and the time is 10-240 min, for example, 10 min, 50 min, 100 min, 150 min, 200 min, 240 min, etc.; the drying temperature is 60-100℃, for example, 60℃, 70℃, 80℃, 90℃, 100℃, etc.
[0041] In a preferred embodiment of the present invention, the preparation method of the modified lithium cobalt oxide cathode material includes the following steps: (1) The raw material rare earth source and LCO cathode material are mixed in a certain proportion, and an appropriate amount of ethanol is added. The mixture is then ball-milled and dispersed, and then dried to obtain a well-dispersed mixed powder.
[0042] (2) Transfer the above mixed powder into a tube furnace and calcine it under a continuous air atmosphere, heat it to the target temperature and keep it at that temperature for a period of time.
[0043] (3) The calcined powder was ball-milled again, washed with ethanol and centrifuged to remove residual impurities, and then dried.
[0044] The present invention also provides the application of a modified lithium cobalt oxide cathode material or a modified lithium cobalt oxide cathode material prepared by the above preparation method in the preparation of lithium-ion batteries.
[0045] The present invention will be further illustrated by the following examples. Unless otherwise specified, the materials in the examples are prepared according to existing methods or purchased directly from the market.
[0046] The LCO cathode material used in the following examples is a commercially available single-crystal LCO material with the following specific parameters: D10 is 4 µm, D50 is 15 µm, D90 ≤ 25 µm, and tap density ≥ 2.7 g / cm³. 3 Specific surface area 0.15 m² 2 / g. The nominal specific capacity is 202mAh / g (2.5-4.6 V).
[0047] Example 1 This embodiment provides a modified lithium cobalt oxide cathode material, the preparation process of which is as follows: S1. A mixture of rare earth nitrate raw materials Gd(NO3)3, La(NO3)3, and Ce(NO3)4 in a mass ratio of 1:1:1 was mixed with LCO cathode material (the rare earth nitrate raw materials accounted for 1% of the total mass of the rare earth source and LCO cathode material). After adding ethanol as a dispersant, the mixture was ball-milled and dispersed. During the ball milling process, the mass ratio of the mixture to the ball to the dispersant was 1:5:5. The differential ball milling speed was 800 r / min, and the ball milling time was 120 min. Subsequently, the mixture was placed in an oven and dried at 80℃ for 12 h to obtain a well-dispersed mixed powder.
[0048] S2. Transfer the above mixed powder into a tube furnace and calcine it under a continuous air atmosphere. Heat it to 600°C at a heating rate of 5°C / min and hold it at that temperature for 7 hours.
[0049] S3. The calcined powder was ball-milled again (ball mill speed was 6 r / min, ball milling time was 120 min), washed with ethanol and centrifuged 3 times to remove residual impurities, and dried overnight in a vacuum oven at 80°C to obtain the modified lithium cobalt oxide cathode material with a particle size of 2-20 µm and a coating thickness of 3-5 nm.
[0050] Example 2 This embodiment provides a modified lithium cobalt oxide cathode material, the preparation process of which differs from that of Example 1 in that: In S1, rare earth raw materials are mixed with LCO cathode material, ethanol is added and ultrasonically dispersed, the treatment time is 120 min, and then dried. In S3, the calcined powder is washed with ethanol and centrifuged several times before being transferred to a ball mill for ball milling and dispersion, and then dried. The modified lithium cobalt oxide cathode material was finally obtained, with a particle size of 2-20 µm and a coating thickness of 0-5 nm.
[0051] Example 3 This embodiment provides a modified lithium cobalt oxide cathode material, the preparation process of which differs from that of Example 1 in that: In S1, rare earth raw materials are mixed with LCO cathode material, ethanol is added and ultrasonically dispersed, the treatment time is 120 min, and then dried. In step S2, the mixed powder obtained in step S1 is transferred into carbon paper and heated to 600°C within 20 seconds using a Joule heating device and held at that temperature for 30 seconds.
[0052] In S3, the calcined powder is washed with ethanol, centrifuged several times, and then dried. The modified lithium cobalt oxide cathode material was finally obtained, with a particle size of 2-20 µm and a coating thickness of 0-2 nm.
[0053] Example 4 This embodiment provides a modified lithium cobalt oxide cathode material, the preparation process of which differs from that of Example 1 in that: the rare earth nitrate raw material accounts for 0.1% of the total mass of the rare earth source and the LCO cathode material; The modified lithium cobalt oxide cathode material was finally obtained, with a particle size of 2-20 µm and a coating thickness of <1 nm.
[0054] Example 5 This embodiment provides a modified lithium cobalt oxide cathode material, the preparation process of which differs from that of Example 1 in that: the rare earth nitrate raw material accounts for 0.5% of the total mass of the rare earth source and the LCO cathode material; The modified lithium cobalt oxide cathode material was finally obtained, with a diameter of 2-20 µm and a coating thickness of 0-2 nm.
[0055] Example 6 This embodiment provides a modified lithium cobalt oxide cathode material, the preparation process of which differs from that of Example 1 in that: the rare earth nitrate raw material accounts for 2% of the total mass of the rare earth source and the LCO cathode material; The modified lithium cobalt oxide cathode material was finally obtained, with a particle size of 2-20 µm and a coating thickness of 5-8 nm.
[0056] Example 7 This embodiment provides a modified lithium cobalt oxide cathode material, the preparation process of which differs from that of Example 1 in that: the rare earth nitrate raw material accounts for 3% of the total mass of the rare earth source and the LCO cathode material; The modified lithium cobalt oxide cathode material was finally obtained, with a particle size of 2-20 µm and a coating thickness of >10 nm.
[0057] Example 8 This embodiment provides a modified lithium cobalt oxide cathode material, the preparation process of which differs from that of Example 1 in that the rare earth raw material is replaced with an oxide (Gd2O3). The modified lithium cobalt oxide cathode material was finally obtained, with a particle size of 2-20 µm and a coating thickness of <1 nm.
[0058] Example 9 This embodiment provides a modified lithium cobalt oxide cathode material, the preparation process of which differs from that of Example 3 in that: S1, the rare earth raw material accounts for 0.5% of the total mass of the rare earth source and the LCO cathode material; In S2, heat to the target temperature of 850℃ and hold for 1 hour; The modified lithium cobalt oxide cathode material was finally obtained, with a particle size of 2-20 µm and a coating thickness of <1 nm.
[0059] Example 10 This embodiment provides a modified lithium cobalt oxide cathode material, the preparation process of which differs from that of Example 3 in that: S1, the rare earth raw material accounts for 2% of the total mass of the rare earth source and LCO cathode material; In S2, heat to the target temperature of 350℃ and hold for 13 hours; The modified lithium cobalt oxide cathode material was finally obtained, with a particle size of 2-20 µm and a coating thickness of 0-3 nm.
[0060] Comparative Example 1 This comparative example provides a commercial LCO, the model of which is the same as the commercial LCO used in Example 1.
[0061] Test Method: CR2016 coin cells were assembled, and the electrochemical performance of the cathode material was tested. The cathode active material, Super P conductive carbon, and PVDF binder were mixed uniformly in NMP solvent at a mass ratio of 8:1:1 to prepare the cathode slurry. The slurry was coated onto an aluminum foil current collector using a doctor blade coating process and vacuum dried at 105℃ for 12 h to remove residual solvent, yielding the working electrode. Using lithium metal as the counter electrode, the coin cell was assembled in an argon glove box with water and oxygen contents both below 1 ppm.
[0062] The test results are shown in Table 1.
[0063]
[0064] Figure 1 The image shows a TEM image of the original commercial LCO cathode material in Comparative Example 1 and the rare earth modified LCO cathode material prepared in Example 1. The modified LCO material shown in the image has a coating layer structure on its surface. Figure 2 The first charge-discharge curves of the original commercial LCO cathode material in Example 1 and the rare earth modified LCO cathode material prepared in Example 1 are shown. Figure 3 The graph shows the cycle discharge capacity curves of the original commercial LCO cathode material in Example 1 and the rare earth modified LCO cathode material prepared in Example 5. Figure 4 The diagram shows the rate discharge capacity of the original commercial LCO cathode material in Example 1 and the rare earth modified LCO cathode material prepared in Example 1. The modified material showed improved discharge specific capacity at all rates measured in this experiment compared to the unmodified material. Figure 5 This is a SEM image of the original commercial LCO cathode material. Figure 6 This is a SEM image of the rare earth modified LCO cathode material prepared in Example 1.
[0065] As shown in Table 1 and the figures, Example 1 represents the preferred process conditions of this invention, effectively improving cycle stability while maintaining the original LCO structure. Examples 1 and 4-10 demonstrate that the modified materials prepared using the preferred rare earth raw material amounts and process conditions within the scope of this invention exhibit higher cycle stability.
[0066] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, and not to limit them; although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some or all of the technical features; and these modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A modified lithium cobalt oxide cathode material, characterized in that, The modified lithium cobalt oxide cathode material uses commercial lithium cobalt oxide as a matrix, the surface of which has a rare earth coating layer, and at least some rare earth elements are incorporated into the crystal lattice of the commercial lithium cobalt oxide.
2. The modified lithium cobalt oxide cathode material according to claim 1, characterized in that, The rare earth coating layer includes one or more of La2O3, CeO2, Gd2O3, and Y2O3.
3. The lithium cobalt oxide cathode material according to claim 1, characterized in that, The particle size of the lithium cobalt oxide cathode material is 2-20 µm; Preferably, the thickness of the rare earth coating layer is 3-8 nm, and more preferably 3-5 nm.
4. The method for preparing the modified lithium cobalt oxide cathode material according to any one of claims 1-3, characterized in that, include: (a) A rare earth source is mixed with commercial lithium cobalt oxide to obtain a mixture; (b) The mixture is subjected to heat treatment to obtain the modified lithium cobalt oxide cathode material.
5. The method for preparing the modified lithium cobalt oxide cathode material according to claim 4, characterized in that, The rare earth source includes rare earth oxides and / or rare earth nitrates; Preferably, the rare earth oxide includes one or more of La2O3, CeO2, Gd2O3, and Y2O3; Preferably, the rare earth nitrate includes one or more of La(NO3)3, Ce(NO3)4, Gd(NO3)3 and Y(NO3)3.
6. The method for preparing the modified lithium cobalt oxide cathode material according to claim 4, characterized in that, The rare earth source accounts for 0.1%-3% of the total mass of the mixture, more preferably 0.5%-2%.
7. The method for preparing the modified lithium cobalt oxide cathode material according to claim 4, characterized in that, In step (a), the mixing is carried out in the presence of a dispersant, which includes at least one of ethanol and deionized water; Preferably, in step (a), the mixing time is 10-240 min; the mixing method includes ball milling and / or ultrasonic treatment, and the ball milling speed is 400-1200 r / min.
8. The method for preparing the modified lithium cobalt oxide cathode material according to claim 4, characterized in that, In step (b), the heat treatment includes: heating to a target temperature and then holding at that temperature; Preferably, the target temperature is 400-800℃, the heating rate is 3-10℃ / min, and the holding time is 2-12h.
9. The method for preparing the modified lithium cobalt oxide cathode material according to claim 4, characterized in that, The heat treatment is followed by a post-treatment process; the post-treatment process includes at least one of ball milling, washing, centrifugation, and drying. Preferably, the ball mill rotates at a speed of 400-800 r / min for 10-240 min. Preferably, the drying temperature is 60-100°C.
10. The application of the modified lithium cobalt oxide cathode material according to any one of claims 1-3 or the modified lithium cobalt oxide cathode material prepared by the preparation method according to any one of claims 4-9 in the preparation of lithium-ion batteries.
Citation Information
Patent Citations
High-capacity and high-compaction density composite lithium cobaltate positive electrode material preparation method
CN106277070A
Lithium cobalt oxide high-entropy doped positive electrode material and preparation method thereof, lithium ion battery and electric device
CN121964626A